Real time monitoring of fs laser annealing on indium tin oxide. (April 2019) - Wu, Ping-Han; Hu, Chih-Lin; Feng, Shih-Wei; Young, Hong-Tsu; Lu, Ming-Yen; Wang, Hsiang-Chen
Highlights: Time-resolved pump-probe system is used to monitoring the femtosecond laser annealing of indium tin oxide. The transmittance variation detected by the probe beam gradually increases with increasing machining power. The 400-nm probe beam is more sensitive than the 800-nm probe beam in measuring curve variation. Abstract: In this study, a set of time-resolved pump-probe systems for the real-time monitoring of femtosecond (fs) laser annealing of ITO substrates is established. A pump beam is used as the light source for thermal annealing, and a probe beam is used to monitor the transmittance variation of ITO in real time. Measurement results show that with increasing machining energy, the transmittance variation detected by the probe beam gradually increases. When the laser energy is small, the transmittance changes arithmetically. When the laser energy is sufficient to complete the modification of ITO, the transmittance variation rises suddenly and sharply, indicating that the thermal annealing modification has been completed in the irradiated area. Then, the laser source is shut down to achieve real-time monitoring. Degenerate and non-degenerate pump-probe experimental results indicate that the 400-nm probe beam is more sensitive than the 800-nm probe beam in measuring curve variation because the variation in the ITO transmission spectrum in the 400-nm wave band is greater than that in the 800-nm wave band. Electron backscatter diffraction analysis indicates that the crystallographic directions of ITO after laser annealing are consistent. This shows that the ITO changed from non-crystallized to crystallized after being irradiated by the pump beam, confirming the thermal annealing modification.